1980
DOI: 10.1177/28.7.6967079
|View full text |Cite
|
Sign up to set email alerts
|

In vitro hippocampal uptake of tritiated serotonin (3H-5HT): A morphological, biochemical, and pharmacological approach to specificity.

Abstract: The in vitro uptake of tritiated serotonin (3H-5HT) into hippocampal slices was measured in Ringer's solution (37#{176}C) containing pargyline, ascorbic acid, and dextrose. The specific uptake of 3H-5HT rose asymptotically as the 3H-5HT molarity was increased from 5 x 1O #{176}to 1.5 x lO M. Linear regression analysis gave a Km value for the specific uptake of 1.4 x 1O M. The nonspecific binding (NSB) was the amount of 3H-5HT retained by the slices following incubation in a medium with a very large excess of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1980
1980
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…The high-affinity uptake of 'H-5-HT was reduced to 15% of control in the whole hippocampus more than 40 days after lesion in both sham and bilaterally adrenalectomized rats. Previous re ports from our laboratory showed that dorsal hippocampal serotonergic fibers are almost completely eliminated by our triple-injection procedure [5]. The deafferentation of sero tonergic fibers leads to a shift in the septal driving of hippo campal theta rhythm to a minimal threshold at 6.9 Hz after 5,7-DHT injections.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The high-affinity uptake of 'H-5-HT was reduced to 15% of control in the whole hippocampus more than 40 days after lesion in both sham and bilaterally adrenalectomized rats. Previous re ports from our laboratory showed that dorsal hippocampal serotonergic fibers are almost completely eliminated by our triple-injection procedure [5]. The deafferentation of sero tonergic fibers leads to a shift in the septal driving of hippo campal theta rhythm to a minimal threshold at 6.9 Hz after 5,7-DHT injections.…”
Section: Discussionmentioning
confidence: 96%
“…Anatomical studies have shown that serotonergic fibers innervate both the granule and pyr amidal neurons in the hipocampus [5,6,17], These same cells have been shown to concentrate circulating 'H-corticosterone [12]. Thus, the same neurons may be responsive to changes in both endocrine and neuronal factors.…”
Section: Discussionmentioning
confidence: 99%
“…The specific serotonin neurotoxin, 5,7-dihydroxytryptamine (5,7-DHT) (Azmitia & Marovitz 1980) was dissolved to a final concentration of 5 x IO"4 mol/1 in Krebs Ringer bicarbonate buffer (KRBH), pH 7.4, supplemented with ascorbic acid (10~3 mol/1) as an antioxidant and the monoamine oxidase inhibitor, parglyline (10~4 mol/1). Rats were anaesthetized with ether and the pancreas was exposed through a midline laparatomy.…”
Section: Ablation Of 5-ht Nervesmentioning
confidence: 99%
“…Similar sized pieces of parietal cortex were taken for use as unincubated controls. The assay procedure has been described previously [7,40].…”
Section: H-5-ht Reuptakementioning
confidence: 99%